2020
DOI: 10.3390/diagnostics10020095
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Complex Regional Pain Syndrome I Following Traumatic Axonal Injury of the Corticospinal Tract in a Patient with Mild Traumatic Brain Injury

Abstract: A 54-year-old male suffered from direct head trauma resulting from a fall while working. At approximately two months after the accident, he began to feel pain (burning sensation) and swelling of the dorsum of the right hand and wrist. He showed the following clinical features among the clinical signs and symptoms of revised diagnostic criteria for complex regional pain syndrome (CRPS): spontaneous pain, mechanical hyperalgesia, vasodilation, skin temperature asymmetries, skin color changes, swelling, motor wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…DTT was used to demonstrate STT injury in relation to central pain ( Jang et al, 2019a ; Jang and Lee, 2019 ) and to find out STT injury in patients who had atypical type of central pain including abdominal pain ( Jang et al, 2020 ). Interestingly, CST damage was revealed using DTT in patients with CRPS following mild TBI ( Jang and Seo, 2020 ). These studies showed that DTT was useful in detecting STT injuries in patients with central pain after TBI.…”
Section: Diffusion Tensor Tractography For Diagnosis Of Various Types Of Neuropathic Painmentioning
confidence: 99%
“…DTT was used to demonstrate STT injury in relation to central pain ( Jang et al, 2019a ; Jang and Lee, 2019 ) and to find out STT injury in patients who had atypical type of central pain including abdominal pain ( Jang et al, 2020 ). Interestingly, CST damage was revealed using DTT in patients with CRPS following mild TBI ( Jang and Seo, 2020 ). These studies showed that DTT was useful in detecting STT injuries in patients with central pain after TBI.…”
Section: Diffusion Tensor Tractography For Diagnosis Of Various Types Of Neuropathic Painmentioning
confidence: 99%
“…The DTI was performed twice (at one month and nine years after ICH onset). On both occasions, a sensitivity-encoding head coil on a 1.5-T Philips Gyroscan Intera scanner (Hoffman-LaRoche Ltd., Best, Netherlands) with single-shot echo-planar imaging and navigator echo was used for the acquisition of DTI data.67 contiguous slices were obtained parallel to the anterior commissure–posterior commissure line for each of the 32 non-collinear diffusion-sensitizing gradients [ 13 ]. DTI parameters were as follows: acquisition matrix = 96 × 96; reconstructed matrix = 128 × 128; field of view = 221 mm × 221 mm; repetition time = 10,726 ms; echo time = 76 ms; parallel imaging reduction factor = 2; echo-planar imaging factor = 49; b = 1000 s/mm 2 ; number of excitations = 1; and slice thickness of 2.3 mm with no gap (acquired voxel size 1.25 mm × 1.25 mm × 2.5 mm) [ 13 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…On both occasions, a sensitivity-encoding head coil on a 1.5-T Philips Gyroscan Intera scanner (Hoffman-LaRoche Ltd., Best, Netherlands) with single-shot echo-planar imaging and navigator echo was used for the acquisition of DTI data.67 contiguous slices were obtained parallel to the anterior commissure–posterior commissure line for each of the 32 non-collinear diffusion-sensitizing gradients [ 13 ]. DTI parameters were as follows: acquisition matrix = 96 × 96; reconstructed matrix = 128 × 128; field of view = 221 mm × 221 mm; repetition time = 10,726 ms; echo time = 76 ms; parallel imaging reduction factor = 2; echo-planar imaging factor = 49; b = 1000 s/mm 2 ; number of excitations = 1; and slice thickness of 2.3 mm with no gap (acquired voxel size 1.25 mm × 1.25 mm × 2.5 mm) [ 13 ]. By using the fiber assignment continuous tracking algorithm, fiber tracking was performed within the diffusion tensor imaging task card software (Philips Extended MR Work Space 2.6.3, Philips, Amsterdam, Netherlands), and the DTI parameters (fractional anisotropy [FA], mean diffusivity [MD], and fiber number [FN, total voxel number of a neural tract]) were automatically calculated using PRIDE software (Philips Medical Systems, Best, Netherlands) [ 13 ].…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations